Studi Kitab Hadis Telaah terhadap Manhaj Kitab Sunan Abu Dawud - Amin, Muhammad (FDIK IAIN Padangsidimpuan, 2019)
Imam Abu Dawud took the style of manhaj with fiqh which began from the book of Taharah and was closed with the book adab. The number of books in the discussion amounted to 36 books, with 1,871 chapters, with the number of hadiths of 5274. Abu Dawud chose his manhaj style with fiqh style so that it would make it easier for people to understand the fiqh problems systematically starting from taharah to adab, while making it easier for the people to find the legal traditions needed. Of course, the manhaj Abu Dawud is inseparable from the shortcomings of the other Imam Hadith manhaj, such as the unavailability of traditions related to the jurisprudence, and not the collection of a valid hadith value in the book